Active surveillance is suitable for intermediate term follow‐up of renal oncocytoma diagnosed by percutaneous core biopsy. (26th July 2016) - Liu, Shuo; Lee, Stephen; Rashid, Prem; Bangash, Haider; Hamid, Akhlil; Lau, Jason; Cohen, Ronald
Abstract : Objectives: To evaluate the intermediate outcome of conservative management in patients with biopsy‐proven oncocytoma. Patients and Methods: Patients with oncocytoma diagnosed on percutaneous core biopsy between January 2000 to December 2014 were identified from the renal biopsy database of a large specialist urologic pathology laboratory. After review of patient clinical records, the study cohort comprised only of patients enrolled in active surveillance. Clinicopathological and follow‐up details were reviewed for each case, in particular: type and interval of surveillance imaging, tumour growth, definitive intervention and reason for intervention. Where possible, correlation was made between the final surgical and the initial biopsy specimens. Results: Fifty three patients diagnosed with oncocytoma on core biopsy were initially placed on active surveillance with median follow‐up of 34 months (range 6–109). The median age at diagnosis was 65 years (range 20–85) and median tumour size was 30 mm (range 13–87). Mean average tumour growth was 1.4 mm per annum (median 0 mm/year) with the majority (36 of 53, 68%) exhibiting minimal growth (less than 2 mm per annum) or partial regression. Forty seven of the 53 patients remained on active surveillance with no significant progression. Six patients elected to undergo definitive intervention (five surgical excision, one ablation). Renal oncocytoma was confirmed in all five patients who underwent surgical excision of their lesions. Conclusions: The majority of oncocytomas in this study showed minimal growth rate or regression. Patients with biopsy proven oncocytoma can be conservatively managed with active surveillance.